EARLY CHILDHOOD EDUCATION IN TIMES OF PANDEMIC IN SCIENTIFIC JOURNALS (2021 TO 2023) - de Jesus Brandão, Isabel Cristina; Leão de Aquino, Ligia Maria (Revista Binacional Brasil-Argentina: Dialogue between the sciences, 2023)
In this article, we aim to analyze four articles that were published from January 2022 to April 2023 on early childhood education and the COVID-19 pandemic. This research is configured as a documental study of an exploratory and qualitative nature, having as source the website of the Scientific Electronic Library Online (SciELO). We used the descriptor early childhood education and pandemic and located a total of nine works, of which three are about research in the field of health, one presents data from a longitudinal study with children from kindergarten carried out between 2017 and 2018, one about digital influencer children and four address early childhood education in the context of the pandemic. The works analyzed show several conflicts experienced by professionals and children in early childhood education in the first two years of the COVID-19 pandemic. The omission of the federal government; the absence of integrated public policies; the ills of the population; the presence of digital technologies as the main working tool; and the role of families as mediators in the teaching-learning process established between school and children.